Pathways connecting socioeconomic variables, substance abuse and gambling behaviour: a cross-sectional study on a sample of Italian high-school students - Roberta Pacifici; Alessandra Buja; Vincenzo Baldo; Claudia Mortali; Luisa Mastrobattista; Adele Minutillo; Simona Pichini; Bruno Genetti; Paolo Vian; Alessandra Andreotti; Giulia Grotto (BMJ Open)
Objectives The aim of this study was to elucidate the pathway of associations linking gambling, alcohol intake, smoking habit, cannabis consumption between each other and with demographic and socioeconomic variables.Setting and participants A survey was conducted in 2017 on a representative sample of 15 602 Italian 14-year-olds to 17-year-olds attending 201 secondary schools.Outcome measures Structural Equation Models analysis was used to assess the pathway between gambling, alcohol intake, smoking, cannabis consumption, demographics and socioeconomic factors.Results Irrespective of socioeconomic or demographic variables, gambling is positively associated with alcohol and cannabis consumption, while cannabis consumption is predicted by smoking and by alcohol intake, smoking is predicted by alcohol intake. Adolescents with a higher weekly income are more at risk of gambling, drinking alcohol and smoking, while the degree of economic dissatisfaction was positively associated with alcohol intake, cannabis consumption and smoking. Maternal employment appeared to be positively associated with adolescents’ smoking, alcohol intake and cannabis consumption.Conclusions This is one of the first studies to shed light on the pathways of associations connecting various health-risk behaviours among adolescents with demographic and socioeconomic factors.